Characterisation and Classification of some Upland Soils - Das, S. N.; Roy, B. B. (Indian Forester, 1982)
Three upland soils of red and lateritic region of Hirbhum district have been classifier after proper characterisation. These soils develop in high temparature regime which falls in hyperthermic group. Morphological descriptions, physico-chemical, physical and mineras logical properties of soil profiles have been cited for proper characterisation. Argillans are present in soil profile No. I and 3, illuviation of silicate clay down the profile produces argillic horizon, leaching is more pronounced in profile No.3 than soil profile No. 1. Soil profil. No. 1 and 2 fall in the coarse loamy group of textural class whereas soil profile No. 1 Falls in fine loamy group. Soils of all the three profiles are dominant with illite clay and the mineralogy class is illitle, All these properties suggest, the soil of profile No.1 and 1 are member of course loamy, illitis, hyperthermic family of Typic Haplustult and Paralithic Ustorthent respectively whereas the soil of profile No.3 is a member of fine loamy illitic, hyperthermic family of Ultic Haplustalf. These classifications of upland soils will certainly give an adequate information for vastly afforested areas of Birbhum district of West Bengal for management purposes.